On the Primary Decomposition of k-Ideals and Fuzzy k-Ideals in Semirings. Issue 2 (3rd April 2021) - Sharma, Ram Parkash; Dadhwal, Madhu; Sharma, Richa; Kar, S.
Abstract : Observing that every k -irreducible ideal of a semiring R is a k -primary ideal, if R is an additively cancellative, yoked and commutative Noetherian semiring, we establish the primary decomposition and uniqueness of the primary decomposition of k -ideals of such semirings. Finally, the primary decomposition and uniqueness of primary decomposition proved for k -ideals is also generalised for fuzzy k -ideals of these semirings.